2010
DOI: 10.1016/j.compscitech.2010.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of epoxy functionalized graphite nanoparticles and the physical properties of epoxy matrix nanocomposites

Abstract: Young's modulus by 50%. These results were realized without compromise to the resin toughness.35

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(43 citation statements)
references
References 28 publications
2
40
0
1
Order By: Relevance
“…Two landmark studies include: (1) [96] NIA NIA t4. 9 Miller et al [97] 1 wt?? 52 % t4.10 Rafiee et al [48] 0.1 Wto?…”
Section: Prospect Of Applicationsmentioning
confidence: 99%
“…Two landmark studies include: (1) [96] NIA NIA t4. 9 Miller et al [97] 1 wt?? 52 % t4.10 Rafiee et al [48] 0.1 Wto?…”
Section: Prospect Of Applicationsmentioning
confidence: 99%
“…However, several studies have focused on improving the dispersion and interface interaction of graphene in a polymeric matrix using functionalised graphene. Novel method for functionalization of GP has been presented by Miller [96] using a coupling agent to form covalent bonding between fillers and soft matrix (0.78 GPa Young's modulus), resulting in 50% modulus improvement at 1 wt % filler fraction. Chiang and Hsu [97] have improved the fire resistance of epoxy/GP nanocomposite following a similar method.…”
Section: Graphene As Green Corrosion Inhibitor In Anticorrosion Coatingmentioning
confidence: 99%
“…The high aspect ratio of the CNTs, the high surface area (high interfacial area between nanofiller and polymer) and their excellent mechanical properties: elastic modulus of around 0.8 TPa, tensile strength of around 150 GPa and elongation at break larger than 10%, contributed to the increase of the tensile properties of the epoxy gelcoats [27][28][29][30]. While the layered exfoliated structure and the platelet shape of the nanographite is responsible for the enhanced tensile properties [31][32][33][34]. The reinforcing mechanisms of ceramic fillers like the titanium dioxide and the montmorillonite clay that were used in the present study have been attributed to their large surface area and surface reactivity of the inorganic phase, the corresponding restricted mobility of the polymer chains and to the increase in the effective particle volume fraction in the nanocomposite [35][36][37].…”
Section: Resultsmentioning
confidence: 99%
“…CNTs are able to create a critical path to diffuse thermal energy at this loading level. Based on an experimental study on thermally conductive composites filled with platelet-shaped boron nitride particles, it was suggested that fillers with platelet shape offer advantages over other spherical or cylindrical morphologies because they can overlap with a large contact area permitting much closer contact between adjacent platelets and reducing the thermal contact resistance [17,[34][35][36][37][38][39]. In addition, Table 4 depicts the data obtained for the coefficient of linear thermal expansion (CLTE) tests.…”
Section: Resultsmentioning
confidence: 99%